(untitled) (Satyawati Nagar, Delhi, 2000)
Contents of material: 1/ Cataloguing technologies. 2/ Online catalogues. 3/ User catalogues. 4/ Groundwork for OPAC design. 5/ Usage data for online catalogues. 6/ The WLN cataloguing services. 7/ The DDC classification. 8/ The LCC classification. 9/ Subject indexing
Keywords: Classification,Library science,Cataloguing; Books